Evaluation of the diet of crossfit participants in a Crossfit affiliate box in Sofia, Bulgaria (Research Announcements "Heritage BG", 2025)
The mix of proteins, carbohydrates, and fats properly can maintain good energy level and fast removal of metabolic products. We present the evaluation of the men and women participants diet in a CrossFit affiliate box in Bulgaria. We compare it with the recommendations for high-intensity training. The data were obtained from a questionnaire for nutrition. Energy intake and carbohydrate consumption values were lower than recommended for exercises with high-intensity. The lower carbohydrate intake negatively influences the energy intake but has with no significant risk for the efficient energy provision of the long-term recovery processes. References:Zaykova, Dilyana. Hranitelen rezhim pri sastezateli po borba klasicheski stil ot natsionalno i mezhdunarodno nivo. Predizvikatelstva i perspektivi pred sportnata nauka, 2017, pp. 73-82.Zaykova, Dilyana, i Lyubomir Petrov. "Otsenka na hraneneto pri sportovete kulturizam, vdigane na tezhesti i silov triboy." Predizvikatelstva i perspektivi pred sportnata nauka, Spetsifika na podgotovkata v razlichni sportni distsiplini, 2017, pp. 58-64.Aerenhouts, Dirk, et al. "Energy and Macronutrient Intake in Adolescent Sprint Athletes: A Follow-up Study." Journal of Sports Sciences, vol. 29, no. 1, 2011, pp. 73-82.American College of Sports Medicine and Academy of Nutrition and Dietics, Dietitians of Canada. ACSM, 2016.Burke, Louise, et al. "Carbohydrates for Training and Competition." Journal of Sports Sciences, vol. 9, 2011, pp. 17-27.Escobar, Kurt, et al. "The Effect of a Moderately Low and High Carbohydrate Intake on Crossfit Performance." International Journal of Exercise Science, vol. 9, no. 3, 2016, pp. 460-470.Glassman, Greg. "Meal Plans." CrossFit Journal, vol. 21, 2004, pp. 1-10.Glassman, Greg. "The CrossFit Training Guide." CrossFit Journal, 2010, pp. 1-115.Gleeson, Michael, et al. "Exercise, Nutrition and Immune Function." Journal of Sports Sciences, vol. 22, 2004, pp. 115-125.Harris, J., and Francis Benedict. A Biometric Study of Basal Metabolism in Man. Carnegie Institute of Washington, 1919.Jäger, Ralf, et al. "International Society of Sports Nutrition Position Stand: Protein and Exercise." Journal of the International Society of Sports Nutrition, vol. 14, 2017, pp. 20.Kerksick, Chad, et al. "ISSN Exercise and Sports Nutrition Review Update: Research and Recommendations." Journal of International Society of Sports Nutrition, vol. 15, 2018, pp. 38.Koehler, Karsten, et al. "Low Energy Availability in Exercising Men is Associated with Reduced Leptin and Insulin but not with Changes in Other Metabolic Hormones." Journal of Sports Sciences, vol. 34, 2016, pp. 1921-1929.Kreider, Richard, et al. "ISSN Exercise & Sport Nutrition Review: Research & Recommendations." Journal of International Society of Sports Nutrition, vol. 2, no. 7, 2010, pp. 7.Loveless, Meredith. "Female Athlete Triad." Current Opinion in Obstetrics & Gynecology, vol. 29, 2017, pp. 301-305.McArdle, William, et al. Exercise Physiology, Nutrition, Energy and Human Performance. Seventh edition, Lippincott Williams & Wilkins, 2010.Miteva, Silvia, et al. "Nutrition and Body Composition of Elite Rhythmic Gymnasts from Bulgaria." International Journal of Sports Science & Coaching, vol. 15, no. 1, 2020, pp. 108-116.Phillips, Stuart, and Luc Van Loon. "Dietary Protein for Athletes: From Requirements to Optimum Adaptation." Journal of Sports Sciences, vol. 29, 2011, pp. 29-38.Prentice, A., and S. Jebb. "Beyond Body Mass Index." Obesity Reviews, vol. 2, no. 3, 2001, pp. 141-147.Schaafsma, Gertjan. "The Protein Digestibility-corrected Amino Acid Score." Journal of Nutrition, vol. 130, 2000, pp. 1865-1867.Sousa, Mónica, et al. "Dietary Strategies to Recover from Exercise-Induced Muscle Damage." International Journal of Food Science and Nutrition, vol. 65, no. 2, 2014, pp. 151-163.Stulnig, Thomas. "The Zone Diet and Metabolic Control in Type 2 Diabetes." Journal of the American College of Nutrition, vol. 34, no. 1, 2015, pp. 39-41.Thomas, Travis, et al. "Nutrition and Athletic Performance." Official Journal of the American College of Sports Medicine, vol. 48, no. 3, 2016, pp. 543-568.
Keywords: CrossFit nutrition; energy intake; energy needs; recommendation